2017
DOI: 10.4082/kjfm.2017.38.4.233
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Blood Level of Persistent Organic Pollutants and Common Gastrointestinal Symptoms

Abstract: Background: Persistent organic pollutants (POPs) are toxic materials that cannot be broken down naturally and that easily accumulate in the body. Although several studies have attempted to uncover the effects of POPs on the endocrine and nervous systems and on cancer, few focus on the relationship between low-dose POPs and public health. Here, we attempt to determine the relationship between the level of POPs and common gastrointestinal symptoms, including abdominal discomfort, diarrhea, and constipation. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…For example, recent studies in Bangladesh (Miah, Hoque, Paul, & Rahman, 2014), Thailand (Sapbamrer & Nata, 2014), Tanzania (Manyilizu et al, 2017), and Pakistan (Tarar et al, 2019) have revealed increased incidences of diarrhea (and other ailments) among farmers occupationally exposed to pesticides. A number of studies have found gastrointestinal symptoms including diarrhea statistically correlated with exposure to organochlorine and organophosphorus pesticides, and PCBs^ (Alam et al, 2015;Islam et al, 2018;Kim, Youn, Ko, Lee, & Lee, 2017;Manyilizu et al, 2017;Miah et al, 2014). Phthalates, parabens, and phenols such as bisphenol-A (BPA) are found in a wide variety of consumer products such as plastics, detergents and cleaning products, paints, pharmaceuticals, cosmetics, soaps, toothpaste, and other personal care products (PCPs), and some canned and processed foods.…”
Section: Exposure To Chemical Immunotoxins Linked With Gastroenterimentioning
confidence: 99%
“…For example, recent studies in Bangladesh (Miah, Hoque, Paul, & Rahman, 2014), Thailand (Sapbamrer & Nata, 2014), Tanzania (Manyilizu et al, 2017), and Pakistan (Tarar et al, 2019) have revealed increased incidences of diarrhea (and other ailments) among farmers occupationally exposed to pesticides. A number of studies have found gastrointestinal symptoms including diarrhea statistically correlated with exposure to organochlorine and organophosphorus pesticides, and PCBs^ (Alam et al, 2015;Islam et al, 2018;Kim, Youn, Ko, Lee, & Lee, 2017;Manyilizu et al, 2017;Miah et al, 2014). Phthalates, parabens, and phenols such as bisphenol-A (BPA) are found in a wide variety of consumer products such as plastics, detergents and cleaning products, paints, pharmaceuticals, cosmetics, soaps, toothpaste, and other personal care products (PCPs), and some canned and processed foods.…”
Section: Exposure To Chemical Immunotoxins Linked With Gastroenterimentioning
confidence: 99%